2011
DOI: 10.2147/ijgm.s23829
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of intravenous antibiotic therapy in patients referred for treatment of neurologic Lyme disease

Abstract: BackgroundWe have shown previously that extended intravenous antibiotic therapy is associated with low morbidity and no mortality in patients referred for treatment of neurologic Lyme disease. In this study, we evaluated the benefit of extended intravenous antibiotic therapy in patients with symptoms of neurologic Lyme disease.MethodsPatients with significant neurologic symptoms and positive testing for Borrelia burgdorferi were treated with intravenous antibiotics, and biweekly evaluation of symptom severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Some believe that PTLDS is caused by persistent B. burgdorferi infection stemming from incomplete bacterial eradication by conventional antimicrobial therapy, and long-term antibiotic treatment and/or the use of other antimicrobials has been proposed as a treatment for PTDLS. 90,91 However, the absence of accompanying objective clinical symptoms and laboratory signs of inflammation counter the persistent infection hypothesis. Furthermore, prospective, placebo-controlled clinical trials have demonstrated minimal or no symptomatic improvement after long-term treatment with antibiotics in patients with PTLDS when compared with placebo.…”
Section: Manifestations and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Some believe that PTLDS is caused by persistent B. burgdorferi infection stemming from incomplete bacterial eradication by conventional antimicrobial therapy, and long-term antibiotic treatment and/or the use of other antimicrobials has been proposed as a treatment for PTDLS. 90,91 However, the absence of accompanying objective clinical symptoms and laboratory signs of inflammation counter the persistent infection hypothesis. Furthermore, prospective, placebo-controlled clinical trials have demonstrated minimal or no symptomatic improvement after long-term treatment with antibiotics in patients with PTLDS when compared with placebo.…”
Section: Manifestations and Diagnosismentioning
confidence: 99%
“…99,100 Two assumptions accompany the diagnosis: first, that chronic Lyme disease is caused by ongoing cryptic infection with morphological variants of B. burgdorferi; [101][102][103][104] and second, that this form of infection is unresponsive to conventional antimicrobial treatment, instead requiring longterm therapy with antibiotics of different classes. 91,100,105 In many instances, patients diagnosed with chronic Lyme disease are also diagnosed with chronic co-infections of other tick-borne pathogens. 106 Recent review articles have demonstrated that the current medical literature supports neither a role for persistent infection 107 nor a role for morphological variants of B. burgdorferi in chronic Lyme disease.…”
Section: Chronic Lyme Diseasementioning
confidence: 99%
“…Other studies reiterate the frequency of adverse events in persons with prolonged exposure to IV catheters and antibiotics. In an observational study by Stricker and colleagues, 109 there were 19 potentially life-threatening adverse events among 200 patients on long-term IV antibiotics for the treatment of CLD. These included 4 cases of venous thromboembolic disease, 6 cases of suspected line sepsis, 7 patients with allergic reactions, and 2 who developed ceftriaxone-induced gallbladder disease (both necessitating cholecystectomy).…”
Section: Extended Antibiotics For the Treatment Of Post-lyme Disease mentioning
confidence: 99%
“…The fact that B. burgdorferi shares resistance genes with pathogenic mycobacteria supports the need for doi: 10.7243/2052-5958-1-2 this therapeutic approach [30,31]. It remains to be seen which form of B. burgdorferi is the true culprit in chronic Lyme disease and which form of treatment is most efficacious in clearing both forms of bacteria from patients [32][33][34][35][36][37][38]. …”
Section: Discussionmentioning
confidence: 99%